Studies in Wild Oat Seed Dormancy: II. ACTIVITIES OF PENTOSE PHOSPHATE PATHWAY DEHYDROGENASES - Adkins, Stephen W. (1981)
A selected strain of wild oat (Avena fatua L.) seed has been shown to lose dormancy rapidly during moist soil incubation at 25 C, whereas seed kept similarly at 5 C maintained a high level of dormancy. The activities of cytosolic dehydrogenase enzymes of the pentose phosphate pathway were assayed throughout a period of moist soil incubation at these two temperatures. A distinction was made between extractable dehydrogenases from the embryo and the endosperm regions of the caryopsis. Dehydrogenase activities monitored in seeds incubated at 25 C gradually increased over the course of the investigation. The largest increases in activity occurred during incubation at 5 C, the situation in which dormancy is maintained. No obvious connection could be found between dormancy breakage and increased activity of the pentose phosphate pathway dehydrogenases.